Intravascular papillary endothelial hyperplasia of superior vena cava: a rare cause of the superior vena cava syndrome. Issue 4 (April 1991) - Park, J Y; Chung-Park, M; Snow, M
Abstract : The superior vena cava syndrome associated with an intraluminal vascular proliferative lesion is extremely rare. A case of intravascular papillary endothelial hyperplasia of the superior vena cava causing obstructive symptoms is reported that was successfully managed by surgical excision.